Nashville [videorecording (DVD)] - Arkin, David, 1941-1991; Baxley, Barbara; Beatty, Ned; Black, Karen, 1939-2013; Blakley, Ronee; Brown, Timothy, 1937-2020-; Carradine, Keith, 1949-; Chaplin, Geraldine, 1944-; DoQui, Robert; Duvall, Shelley, 1949-; Garfield, Allen, 1939-2020-; Gibson, Henry; et al. (Criterion collection, 2013)
"[The feature film] weaves the stories of 24 characters--from country star to wannabe to reporter to waitress--into a cinematic tapestry that is equal parts comedy, tragedy, and musical. Many members of the ... cast wrote their own songs and performed them live on location"--Container.